Representing and Implementing Moral Values to Foreign Students in Indonesian Textbooks for Learners Other Than Indonesians - Yuni Pratiwi; Kusubakti Andajani; Imam Suyitno; Asri Ismail; Bambang Prastio (International Journal of Language Education, 2023)
The textbook "Sahabatku Indonesia" published by the Ministry of Education and Culture of the Republic of Indonesia in 2019 has an important position for foreign students who are studying Indonesian. This book consists of 7 series. The book contains information about practical communication rules and exercises in Indonesian. In the communication training material various discourse units are presented which contain information on Indonesian culture. One aspect of culture that is taught is the moral aspect that accompanies language activities. This study aims to describe the representation and implementation of moral values introduced to foreign students in textbooks. These moral values come from moral values that are unique to the Indonesian nation and also universal morals. This research was conducted using a qualitative descriptive approach. The data source for this research is the 7 book series “My Indonesian Friends”. The data is in the form of written verbal units containing moral values and sometimes illustrations are added to accompany the communication exercises. Data were analyzed using content analysis and supported by Appraisal Theory (AT) to see aspects of moral values. This finding illustrated that on "Sahabatku Indonesia" textbook emphasizes inculcating moral values of learners in maintaining harmony and social interactions harmony in their living environment. The moral values contained in the text are as many as 13 moral themes. The implementation in the book can be found in the form of narrative text and picture illustrations. Understanding those moral values made a meaningful contribution to curriculum developers and textbook writers as a basis for consideration in determining their policies.